A method for simultaneously crosslinking and functionalizing extracellular matrix-based biomaterials as bioprosthetic heart valves with enhanced endothelialization and reduced inflammation. (1st January 2021) - Guo, Gaoyang; Jin, Linhe; Wu, Binggang; He, Haiyang; Yang, Fan; Xu, Liangpeng; Lei, Yang; Wang, Yunbing
Abstract: With the coming of an aging society and the emergence of transcatheter valve technology, the implantation of bioprosthetic heart valves (BHVs) in patients with valvular disease has significantly increased worldwide. Currently, most clinically available BHVs are crosslinked with glutaraldehyde (GLUT). However, the GLUT treated BHV is less durable due to the combined effect of multiple factors such as cytotoxicity, immune responses, and calcification. In this study, the in-situ polymerization of sulfonic monomers with a decellularized extracellular matrix (ECM) was performed to simultaneously achieve the crosslinking and functionalization of ECM. Subsequently, the feasibility of the hybrid ECM used as leaflet material of BHV was evaluated. In in-vitro tests, the results indicated that the hybrid ECM fixed collagen efficiently and the introduction of sulfonic polymer promoted the proliferation and migration of human umbilical vein endothelial cells (HUVECs). In in-vivo tests, after being implanted in SD rats and mice, the hybrid ECM significantly inhibited immune response and calcification compared with the non-hybrid counterpart and GLUT crosslinked tissue. These results indicated that the hybrid ECM exhibited more competitive stability and better biocompatibility compared to these features in GLUT-crosslinked valve. Therefore, the sulfonic polymer hybrid ECM provides a potential material for more durable BHV and the in-situ polymerization strategy can serve as a general treatment method for tissue crosslinking as well as tailoring the biophysical properties of ECM.